Impact of Covid-19 on Student Satisfaction Level on Online Learning in Universities - Mastiur Verawaty Silalahi (Universitas Muhammadiyah Mataram, 2021)
The Covid-19 virus has had a very big impact, especially for the world of education. The impact that occurred in the world of education was experienced by several private universities, especially the HKBP Nommensen Pematangsiantar University (UHKBPNP). As a result of the COVID-19 virus, universities are required to make changes to learning procedures that were previously done face-to-face to online learning. However, the challenge for universities is the diversity of origin of the students themselves. This study aims to determine the impact of the Covid-19 pandemic on online learning satisfaction. This study uses a qualitative approach with descriptive analysis. The number of students who were used as informants in this study were 169 people consisting of active students in the Elementary School Teacher Education Study Program, Water Resources Management Study Program and Mathematics study programs who were randomly selected. Based on the results of the study, it is known that the majority of students at UHKBPNP have devices to support online learning, it can be seen from the percentage of device ownership of 94%. However, there are still some dissatisfactions faced by students when online learning is carried out such as: students feel they cannot easily monitor the progress of online learning, cannot obtain learning materials easily nor can they learn material easily. Overall, both from the technology side and the lecturer side, students are not satisfied with the online learning method they are currently living and also dissatisfied with the lecturer's ability to deliver material in online learning.